Implementasi Kolaborasi Akademi Militer Magelang, Politeknik Pariwisata Batam, Dan Universitas Pertahanan Dalam Peningkatan Literasi Sains Melalui Distribusi “Buku Isu Globall” Untuk Perguruan Tinggi Di Indonesia - Dwi Joko Siswanto; Frangky Silitonga; Linus Yosep Wawan Rukmono; Fierman Sjafirial Agustus; Windy Kartika Putri Widayanti; Tjatur Supriyono; Rita Kuntarti; Khairul Muslim (SIGMA : Jurnal Sinergi Mengabdi, 2026)
Science literacy is one of the important competencies that must be possessed by the academic community in dealing with the development of science, technology, and the dynamics of global issues. However, there is still a gap in access to the latest scientific references in various university libraries in Indonesia. This Community Service (PkM) activity aims to improve science literacy through the distribution of ISU GLOBAL: Multidisciplinary Approaches in the Transformation and Development of Global Issues to a number of university libraries in Indonesia. The activity was carried out through a collaboration between the Defense University of the Republic of Indonesia, the Batam Tourism Polytechnic, and the Magelang Military Academy as a form of implementation of the Tri Dharma of Higher Education. The implementation method includes identifying library needs, coordinating with recipient universities, distributing books, handing over collections, and evaluating the use of books as learning references. The results of the activity show that the addition of reference collections on global issues enriches the learning resources of students and lecturers, supports the development of science literacy, and strengthens the reading culture in the university environment. This activity also shows that collaboration between higher education institutions is able to expand the impact of community service in supporting the improvement of the quality of higher education in Indonesia.